Management Team In The Organization - Muh Hisyam; Nur Wahida; Alwan Suban (Business Finence Analyst Co.,, 2025)
Organization is a group of individuals to do work to achieve goals, so the organization will always talk about the team. This paper will discuss team management in the organization. This study uses a library research method. The data analysis technique used is the content analysis technique, which is an analysis technique to find concepts, themes, words, sentences in various sources, such as books, essays, articles, documents and so on. Based on research that has been conducted on books and scientific articles, team management consists of team formation, effective communication, assignment of tasks and responsibilities, encouraging collaboration and teamwork, monitoring and evaluating work, dealing with conflicts within the team, coaching and team building, and building a positive team culture. The things that can affect team management are the level of team development, team cohesion and team norms.